The Potency and Diversity of Genetic Resources of Ongole Cross Breed - Astuti, Maria (Indonesian Animal Sciences Society, 2004)
The populations of Ongole Grade cattle in 1991 reached 4,600,000 heads dominating the number ofbeef cattle in Indonesia and they were concentrated in Java . However, a dramatic decrease occurred and in 2001 it was reported that the population was amounted to 874,000 heads and they were still concentrated in Java . As genetic resources of local cattle the population increase needs to be carried out immediately particularly outside Java island where a large number of Ongole Grade are reared . The biological reproduction and production potency shows a very significant variation, the average performance reported shows that the role of environment is crucial. The Ongole Grade cattle are very sensitive to feed changes and improvements . The averages of Ongole cross breed calf crop community farms that had been reported were 36%, 52.63%, 54 .60%, and 59.32% . The low percentage is due to a long period of gap between calving caused by bad reproduction and mating management. The average value that has been reported for S/C ranges from 1 .29 for the smallest and 2 .23 for the highest, for the shortest period of having a calf is13 .75 months and the longest is 20 .30 months, the shortest period of mating after having a calf is 97.80 days and the longest is 309.00 days. The average values reported for daily weight gain after pre-weaning is 0.62 kg and post weaning is 0.24 kg, for calves ages 4-12 months it ranges from 0.34 to 0.37 kg, for those ages 13 to 24 months it ranges from 0.31to 0.40 kg, for those ages 2 years it ranges from 0.44 to-0 .91kg. The genetic potency of Ongole cross breed cattle has not widely known as the data are not yet available. Performance identification and recording of Ongole cross breed cattle needs to be carried out immediately. Theoretically, it is assumed that the diversity ofgenetic resources of Ongole cross breed cattle is quite extensive as they are less experienced selection. The enhancement of Ongole cross breed cattle productivity is carried out through breeding efforts by taking genetic resources conservation into consideration, and they require sufficient environmental support. The development and conservation regions for Ongole Grade cattle need to be determined by the government policy . In those regions Ongole crossbreed cattle are purely reared and their genetic quality should be improved. Selection method among the population can be carried out and conservation model can imitate P3 Bali model which adopts the Open Nucleus Breeding Scheme (ONBS). The productivity enhancement through cross breeding with exotic stock will only be done with well plan with a certain target . Cross breeding is heterosis, thus cross breeding for beef cattle will only enhance production characteristics, but not the reproduction ones. The interaction between heterosis and the environment is very important, therefore cross breeding between a couple of stock breed in an environment may not suitable in another environment . Estimation on the effect of additive and heterosis is required as a principle consideration in choosing the cross breeding system to be conducted besides the choice on the exotic breed, which recently tends to use Europe Bos taurus . Key words: Ongole Grade cattle, animal genetic resources